The impact of climate change on labour demand in the plantation sector: the case of tea production in Sri Lanka1. (29th May 2018) - Gunathilaka, Rajapaksha P. D.; Smart, James C. R.; Fleming, Christopher M.; Hasan, Syezlin
Abstract : Limited opportunities for crop switching and lengthy preharvesting periods make the plantation sector particularly vulnerable to climate change. Surprisingly, however, the economic consequences of climate change on plantation crops are seldom analysed. Drawing on a unique primary panel data set from a representative cross section of 35 tea estates in Sri Lanka over the period 2002–2014, this study implements a structural model of estate profit maximisation to estimate the elasticity of labour demand with respect to different components of weather. Results indicate a negative relationship between labour demand and rainfall in the south‐west monsoon, the north‐east monsoon and the second inter‐monsoon. A positive relationship is found between labour demand and rainfall in the first inter‐monsoon. Overall, predicted changes in rainfall by 2050 are anticipated to reduce labour demand by approximately 1, 175, 000 person‐days per year across Sri Lanka's tea plantation sector. This is likely to have considerable social and welfare implications, particularly for the Indian Tamil women who comprise the majority of the sector's workforce.